Privacy-preserving digital rights management scheme in cloud computing - Qin-long HUANG; Zhao-feng MA; Jing-yi FU; Yi-xian YANG; Xin-xin NIU (Tongxin xuebao)
In order to meet the needs of digital content and user privacy protection in cloud computing environment, a privacy-preserving digital rights management (DRM) scheme in cloud computing was proposed. The framework of digital content copyright lifecycle protection and user privacy protection in cloud computing was firstly designed, which includes four protocols: system setup, content encryption, license acquisition and content decryption, and then a content encryption key protection and distribution mechanism based on attribute-based encryption and additively homomorphic encryption was proposed, which ensures the security of content encryption key. In addition, the pro-posed scheme also allows the users to purchase content and acquire license anonymously from cloud service provider, which protects the user privacy and prevents cloud service provider, license server and key server in the cloud from collecting the user's sensitive information. Compared with existing DRM schemes in cloud computing, the proposed scheme which not only protects the data security and user privacy, but also supports fine-grained access control, and supports online and super-distribution application modes, is more applicable in the copyright protection for cloud computing.